A transcriptional and functional analysis of heat hardening in two invasive fruit fly species, Bactrocera dorsalis and Bactrocera correcta - Gu, Xinyue (John Wiley and Sons Inc., 2019)

(untitled) (Evol Appl)
Many insects have the capacity to increase their resistance to high temperatures by undergoing heat hardening at nonlethal temperatures. Although this response is well established, its molecular underpinnings have only been investigated in a few species where it seems to relate at least partly to the expression of heat shock protein (Hsp) genes. Here, we studied the mechanism of hardening and associated transcription responses in larvae of two invasive fruit fly species in China, Bactrocera dorsalis and Bactrocera correcta. Both species showed hardening which increased resistance to 45°C, although the more widespread B. dorsalis hardened better at higher temperatures compared to B. correcta which hardened better at lower temperatures. Transcriptional analyses highlighted expression changes in a number of genes representing different biochemical pathways, but these changes and pathways were inconsistent between the two species. Overall B. dorsalis showed expression changes in more genes than B. correcta. Hsp genes tended to be upregulated at a hardening temperature of 38°C in both species, while at 35°C many Hsp genes tended to be upregulated in B. correcta but not B. dorsalis. One candidate gene (the small heat shock protein gene, Hsp23) with a particularly high level of upregulation was investigated functionally using RNA interference (RNAi). We found that RNAi may be more efficient in B. dorsalis, in which suppression of the expression of this gene removed the hardening response, whereas in B. correcta RNAi did not decrease the hardening response. The different patterns of gene expression in these two species at the two hardening temperatures highlight the diverse mechanisms underlying hardening even in closely related species. These results may provide target genes for future control efforts against such pest species.